IMPLEMENTATION OF DYNAMIC ROUTING WITH OSPF (OPEN SHORTEST PATH FIRST) TECHNIQUE IN LOCAL AREA NETWORK (LAN) AT SMKN 2 TELUK KUANTAN - Handika, Marezi; Herwin, Herwin; Haryono, Dwi; Muzawi, Rometdo (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2021)
SMKN 2 Teluk Kuantan has 4 (four) main lines of internet network. Of the four networks have their own configuration. Static routing applied in SMKN 2 Teluk kuantan for the four modems of the network has their own area, because it is not under one control of the modem to the Router. Static Routing in SMKN 2 Teluk Kuantan is very possible to be damaged or trouble itself on the network of each modem. Static routing problems are so complex in the form of routing information into the routing table that is set manually by the network administrator. Dynamic Routing is very possible to be implemented in SMKN 2 Teluk Kuantan. where dynamic routing has a basic routing algorithm of dynamic routing. Dynamic Routing enters routing information into the routing table through exchanging information with other routers and creates routing tables dynamically, on dynamic routing network administrators will not enter the entry route manually into the routing table. Routing Open Short Path First (OSPF) is a type of routing protocol that builds topology independently by choosing the best path then iji network quality if the best path is in interference and perform Quality of Service (QoS) against realtime data.